Effect of long term application of super absorbent polymer on soil structure, soil enzyme activity, photosynthetic characteristics, water and nitrogen use of winter wheat - Yang, Yonghui; Zhang, Sensen; Wu, Jicheng; Gao, Cuimin; Lu, Defu; Tang, Darrell W. S. (Frontiers in Plant Science, 2022)
Water scarcity and seasonal drought are major constraints on agricultural development globally. Super absorbent polymer (SAP) is a good amendment that can improve soil structure, increase soil water retention, and promote crop growth even with less soil moisture. We hypothesize that long term application of SAP has a better effect on soil organic carbon, soil enzyme activity, photosynthetic characteristics, yield, and water and nitrogen use than short term application. A long term field experiment with different application rates (0 (CK), 15 (L), 30 (M), 45 (H) kg ha-1) of SAP was conducted at the Yuzhou water conservation agriculture base of the Henan Academy of Agricultural Sciences from 2011 to 2019. The results indicate that applying SAP increases > 0.25 mm aggregates and decreased <0.25 mm aggregates in the soil after one year (2011) and 9 years (2019) of application. In addition, soil organic carbon, soil microbial biomass carbon, soil sucrase and cellulase activities, soil water consumption, water consumption, net photosynthetic rate (Pn), leaf water use efficiency (LWUE) of wheat and yield, all increased after SAP application. SAP also boosts water use efficiency and nitrogen use efficiency. SAP treatment at a dosage of 45 kg ha-1 is most effective and is thus recommended. Correlation analyses show that SAP promotes the growth of wheat, and improves the utilization rate of soil water and nutrients by improving the soil structure and increasing soil organic carbon and microbial enzyme activity.